PENINGKATAN HASIL BELAJAR IPA MATERI SISTEM GERAK PADA MANUSIA MELALUI MODEL PEMBELAJARAN INKUIRI TERBIMBING DENGAN PENDEKATAN SCIENTIFIC PADA SISWA KELAS VIII-D SMP NEGERI 2 ALALAK - Sukatno Sukatno (Fakultas Tarbiyah dan Keguruan UIN Antasari, 2023)
The purpose of the study was to determine the science learning outcomes of the Motion System Material in Humans through the Guided Inquiry Learning model with a Scientific Approach for students in class VIII-D SMP Negeri 2 Alalak Barito Kuala Regency. This class action research follows the following procedure: (1) planning, (2) action implementation, (3) observation, (4) reflection. This research took place in Class VIII-D SMP Negeri 2 Alalak, Barito Kuala Regency, the research time from August 23 to October 19, 2022, while the research subjects were 28 students. The results showed that, cycle I teacher activity reached 74.07% with a good category (B) in cycle II increased to 88.89% with a very good category (SB). Student activity in participating in learning cycle I average 67.71% with good category (B) in cycle II increased to 90.63% with very good category (SB). While the learning outcomes of cycle I average value 74.84, in cycle II it increased to 82.66. Learning completeness in cycle I there were only 18 students (62.50%) complete, increased in cycle II to 26 students (93.75%) complete, only 2 students (6.25%) were declared incomplete.